Negotiating Love, Rahmah, And Adab: Humanizing Islamic Religious Education In Indonesian Higher Education - Desy Meyrina; Ani febriance; Nova Emiria; Ani da; Dara Paradilla; Dwi Noviatul Zahra; Tri Hariyati (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
Abstract: This research aims to understand the integration of the concepts of love (maḥabbah), raḥmah, and adab in the humanization of Islamic Religious Education (PAI) in Indonesian universities. The research is motivated by the tendency of PAI learning to be more oriented towards cognitive aspects, academic achievement, and knowledge transfer so that the spiritual, emotional, and moral dimensions in education are often overlooked. This research uses a qualitative approach with the type of library research through the study of Islamic classical literature, the Qur'an, Hadith, books, and relevant scientific journals. The data analysis technique uses content analysis with an interpretive approach to understand the deep meaning of the concepts of love, raḥmah, and adab in Islamic education. The results of the study show that love (maḥabbah) functions as a spiritual foundation that builds emotional attachment and sincerity in the relationship between lecturers and students, raḥmah is a pedagogical approach based on compassion, empathy, and tenderness that creates a humanistic and inclusive learning atmosphere, while adab becomes an ethical foundation that directs knowledge to the formation of morals and moral responsibility. The integration of these three values forms the paradigm of Islamic Religious Education which is not only oriented towards intellectual intelligence, but also on strengthening spirituality, moral maturity, and the formation of human beings. Thus, the humanization of Islamic education through love, raḥmah, and adab is a relevant approach in responding to moral crises, spiritual droughts, and formalistic educational relations in modern universities.